Matrizes autorais na animação brasileira: identificando a recorrência de características gráficas singulares no desenho do artista animador - Simon Pedro Brethe (2019)
Considering that one of the characteristics of Brazilian animated films is the diversity of visual proposals, this research aims to show the formation of authoring matrices from the identification of singular graphic characteristics recurrent in the animation design, observed in the set of the work of some artists Brazilian animators. The research was divided into three parts. The first chapter was traded about theoretical basis for the ideas of artistic creation, based on the reflections of the artist and researcher Fayga Ostrower, which discusses the role of the contexts experienced by the artist as modellers of their individuality and influencers of their artistic creation. Thus, a method of analysis was proposed to identify unique graphic aspects in the animation design based on the author's ideas. The method considers the primaryobservation of the way in which the animator draws the fundamental graphic elements of visual language (dot, line, surface and color), associating them with three aggregating factors: cultural and artistic reference of interest, supported by technical understanding. In addition, afour-artist a test of reproduction of a drawing that was applied to four artists in four different conditions to demonstrate graphic uniqueness through the way each one designs articulates the fundamental graphic elements. In the second chapter, we sought to define the concept ofauthor and matrix from the authors Marina Estela Graca and Jean-Claude Bernardet, students of experimental animation and authorship in the cinema respectively. It was analyzed the recurrence of singular graphic characteristics in the animation design of the Brazilian author Marcelo Marao 's copyrighted films in order to exemplify the idea of author' s matrix in the context of Brazilian animation. In the third chapter, the analyzes were made of the works of two Brazilian animators, the miner Jackson Abacatu and the Goiano Wesley Rodrigues, to demonstrate the process of development of the author's matrix of these artists. In the finalconsiderations, we sought to reflect on issues involving the creation of the author animator and the context in which he is inserted, that is, in the Brazilian animated film market.